2013
DOI: 10.5194/acp-13-3517-2013
|View full text |Cite
|
Sign up to set email alerts
|

A robust calibration approach for PM<sub>10</sub> prediction from MODIS aerosol optical depth

Abstract: Abstract. Investigating the human health effects of atmospheric particulate matter (PM) using satellite data are gaining more attention due to their wide spatial coverage and temporal advantages. Such epidemiological studies are, however, susceptible to bias errors and resulted in poor predictive output in some locations. Current methods calibrate aerosol optical depth (AOD) retrieved from MODIS to further predict PM. The recent satellite-based AOD calibration uses a mixed effects model to predict location-spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…However, a recent study by Lee et al 20 in the New England region of the United States found that satellite-based AOD predicted surface PM2.5 concentrations with an R 2 of 0.83 using a mixed effects model. Another study by Yap et al 31 in peninsular Malaysia reported an R 2 of 0.88.…”
Section: Discussionmentioning
confidence: 90%
“…However, a recent study by Lee et al 20 in the New England region of the United States found that satellite-based AOD predicted surface PM2.5 concentrations with an R 2 of 0.83 using a mixed effects model. Another study by Yap et al 31 in peninsular Malaysia reported an R 2 of 0.88.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the degree of relationship between the PM and AOD quantities have established by literature. Their relationship can be determined using their level of correlation (Schäfer et al, 2008;Yap and Hashim, 2013). This practical approach is acknowledged for examining PM concentration from satellite remote sensing AOD data.…”
Section: Data Analysis Approachmentioning
confidence: 99%
“…The traditional PM2.5 ground monitoring network provides important space and time information for PM2.5 concentration and composition in the atmosphere. Besides, it has great potential to study air-related climate and air quality issues (Yap et al, 2012). Yet it inevitably has some limitations.…”
Section: Introductionmentioning
confidence: 99%